Mathematical Problem-Solving Beliefs and Metacognitive Awareness: The Moderating Effect of Mathematical Curiosity (American Journal of Multidisciplinary Research and Innovation, 2025)
This study employed a descriptive-correlational design to investigate the moderating effect of mathematical curiosity on the relationship between mathematical problem-solving beliefs and metacognitive awareness among college students enrolled at a private university in Davao City. The respondents were identified through cluster sampling. Results revealed that mathematical problem-solving beliefs significantly predict and moderately positively correlate with metacognitive awareness. Mathematical curiosity also predicts metacognitive awareness. However, mathematical curiosity does not significantly moderate the relationship between mathematical problem-solving beliefs and metacognitive awareness. This suggests that a student’s beliefs in their problem-solving skills remain a crucial aspect of their metacognitive awareness, regardless of their level of curiosity. Further research is recommended to explore students’ gaps, particularly in declarative knowledge and the place of mathematics, and to investigate this study’s best-fit model, notably among math majors.